Proposed modification to IS:456 to predict the shear strength of FRP-reinforced concrete beams - Thomas, Job; Ramadass, S. (Journal of Structural Engineering, 2024)
This paper deals with experimental and analytical study on the shear strength of concrete deep beams reinforced with fibre reinforced polymer (FRP) bars. Eight concrete beams reinforced with glass fibre reinforced polymer (GFRP) rebar were cast and tested over shear span to depth ratio between 0.5 and 1.75. The variables of experimental programme are concrete compressive strength (fck), shear span to depth (a/d) ratio, longitudinal reinforcement ratio (pt) and cross section of the beam. A mathematical model is proposed for the evaluation of shear strength of concrete beams reinforced with FRP bars by modifying the corresponding model given by IS: 456-2000 for steel reinforced concrete beams. The influence of FRP as internal reinforcement is incorporated in the proposed model. The proposed model is developed based on a statistical regression analysis of test data of 188 FRP reinforced beams published in various literatures. The proposed model accounts for compressive strength of concrete (fck), modulus of FRP rebar (Ef), longitudinal reinforcement ratio (pt), shear span to depth ratio (a/d) and size effect of beams. The prediction of shear strength of FRP reinforced concrete beams based on models proposed by various design guidelines and manuals is compared in this paper. The shear strength of FRP reinforced concrete beams predicted using the proposed model is found to be in good agreement with the corresponding test data.